DENND5B Gene Expression as a Trigger for the Development of Diabetes Mellitus–Peripheral Artery Disease: Insights from a Univariate and Multivariate Mendelian Randomization Study - Qiaoqiao Li; Fuli Cao; Xueping Gao; Yuan Xu; Bo Li; Tianyang Hu (Global Heart)
Background: Peripheral artery disease (PAD) is a manifestation of systemic atherosclerosis that can result in limb pain, disability, or mortality. Notably, diabetes mellitus (DM) stands out as one of the most significant risk factors for the development of PAD. Compared to individuals with PAD but no DM, those with concurrent DM and PAD (DM-PAD, diabetes mellitus–peripheral artery disease) face a seven-fold higher risk of critical limb ischemia and a five-fold higher risk of amputation. However, the pathogenic factors and effective therapeutic targets for DM-PAD still remain elusive. Method: To identify candidate hub genes and develop insights into the pathogenesis of DM-PAD, we employed a comprehensive approach encompassing two-sample Mendelian Randomization (two-sample MR), summary data-based Mendelian randomization (SMR), and Bayesian colocalization (COLOC) methods. These methodologies facilitated the integration of summary-level data derived from genome-wide association studies of DM-PAD with expression quantitative trait locus (eQTLs) studies conducted on blood samples. Result: DENND5B, C4A, and CYP21A2 were found to have passed two-sample MR and SMR analyses, indicating their status as hub genes associated with DM-PAD through mechanisms involving not linkage but rather causality. The COLOC analysis provided strong evidence suggesting that DENND5B and the DM-PAD trait were influenced by the common causal variant rs1150948. Conclusion: Our study has pinpointed several crucial genes (DENND5B, C4A, and CYP21A2), notably the DENND5B gene, as potential regulators in the pathogenesis of DM-PAD. These discoveries hold promises for shedding light on the underlying mechanisms and novel targets of the disease in future research.